Adaptations to prey base in the hypercarnivorous leopard cat Prionailurus bengalensis. Issue 4 (3rd July 2020) - Hisano, Masumi; Newman, Chris
Abstract : Investigating biogeographical variations in diet composition can help understand the adaptability and generalism of species. Although the dietary adaptability of omnivorous mesocarnivores is well established, far less work has explored how more specialist hypercarnivores optimise their diets. By reviewing 11 studies of the leopard cat ( Prionailurus bengalensis ), we quantitatively examined how dietary composition varies over the wide range of biomes they occupy in Asia. Specifically, we contrasted the diet of the Iriomote Island sub-species (south-western Japan), where native rodents are absent, with that of the mainland. Leopard cat diet typically comprised mammals, birds, amphibians, reptiles, and invertebrates. In Iriomote Island, however, the low relative frequency of occurrence of small mammals (only introduced rats) was compensated by higher frequencies of reptiles and amphibians compared to the mainland. Consequently, trophic diversity and dietary niche breadth were higher for leopard cats in Iriomote Island than for the mainland. This shows that even hypercarnivorous species can use trophic plasticity to adapt to local prey availability. Given that rodent numbers often fluctuate substantially over time, the availability of alternative prey, such as herptiles, may be vital for the conservation of the leopard cat, and especially the critically endangered Iriomote cat. More generally, the trophic versatility of hypercarnivores must be considered when assessing their vulnerability to environmental change.